(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2022)
Both radical behaviorists and libertarian paternalists propose that scientific knowledge about human behavior be used to modify cultural practices. However, Skinner’s idea of ​​cultural planning has not achieved the same success that Thaler and Sustein’s nudges have achieved in recent years. The purpose of this article is to make a comparison of these two proposals, having in mind, mainly, the epistemological conceptions underlying them. One of the main differences observed concerns the way in which the authors conceive the relationship between basic research and application. This factor seems to be relevant to explain the different levels of social impact obtained by each proposal, but they are not enough. It is also necessary to take into account that Thaler and Sustein’s intervention model can produce effects in larger groups and with less effort than required by the type of intervention idealized by Skinner.